2005
DOI: 10.1158/0008-5472.can-05-0658
|View full text |Cite
|
Sign up to set email alerts
|

WTH3, which Encodes a Small G Protein, Is Differentially Regulated in Multidrug-Resistant and Sensitive MCF7 Cells

Abstract: The WTH3 gene's biological characteristics and relationship to multidrug resistance (MDR) were investigated further. Results showed that WTH3 was mainly located in the cytosol and capable of binding to GTP. In addition, WTH3's promoter function was significantly attenuated in MDR (MFC7/AdrR) relative to non-MDR (MCF7/WT) cells. Advanced analyses indicated that two mechanisms could be involved in WTH3's down-regulation: DNA methylation and trans-element modulations. It was found that the 5Vend portion of a CpG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…Earlier studies suggested that it was a negative regulator for MDR development (Shan et al, 2002a;Tian et al, 2005a, b), which made it extremely interesting as most MDRrelated genes discovered so far exert a positive effect. To understand the mechanisms involved in its downregulation in MDR cells the gene's promoter was identified and analysed (Tian et al, 2005b). We found that it was differentially regulated in MCF7/AdrR and MCF7/WT cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies suggested that it was a negative regulator for MDR development (Shan et al, 2002a;Tian et al, 2005a, b), which made it extremely interesting as most MDRrelated genes discovered so far exert a positive effect. To understand the mechanisms involved in its downregulation in MDR cells the gene's promoter was identified and analysed (Tian et al, 2005b). We found that it was differentially regulated in MCF7/AdrR and MCF7/WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about generating the pcDNA3.1/WTH3 and pGL/WTH3P constructs containing the coding region and WTH3 promoter, respectively, were described previously (Shan et al, 2002a;Tian et al, 2005b). Six deletion mutants of the WTH3 promoter were created by polymerase chain reaction (PCR) amplification using pGL/WTH3P as the template.…”
Section: Construction Of Recombinant Dnamentioning
confidence: 99%
See 3 more Smart Citations